2018
DOI: 10.1111/jnc.14540
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids and neuronal degeneration in lysosomal storage disorders

Abstract: Ceramide, sphingomyelin, and glycosphingolipids (both neutral and acidic) are characterized by the presence in the lipid moiety of an aliphatic base known as sphingosine. Altogether, they are called sphingolipids and are particularly abundant in neuronal plasma membranes, where, via interactions with the other membrane lipids and membrane proteins, they play a specific role in modulating the cell signaling processes. The metabolic pathways determining the plasma membrane sphingolipid composition are thus the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 115 publications
3
41
0
1
Order By: Relevance
“…This temporal relationship raises the possibility that the delay in clinical presentation of those LSDs that impact sphingolipid metabolism could result from the fact that these lipids are not a major constituent of neuronal membranes during development and compensatory mechanisms are operative (Grassi et al . ). Sphingolipids are also critical for remodeling and repair of cell membranes, both at the plasma membrane as well as other organelles.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…This temporal relationship raises the possibility that the delay in clinical presentation of those LSDs that impact sphingolipid metabolism could result from the fact that these lipids are not a major constituent of neuronal membranes during development and compensatory mechanisms are operative (Grassi et al . ). Sphingolipids are also critical for remodeling and repair of cell membranes, both at the plasma membrane as well as other organelles.…”
mentioning
confidence: 97%
“…The LSDs typified by abnormal accumulation of sphingolipids are nicely summarized by Grassi et al . (). It is clear that the blockade of proper sphingolipid metabolism in the context of lysosomal dysfunction leads to more widespread issues with metabolite flow and a better understanding of the complexity of such metabolite crosstalk represents an ongoing challenge in the LSD field.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…As a completely novel and important insight, the mouse data revealed significant accumulations of sphingosines. This elevation is known to occur in cell culture upon serum deprivation [97] and might simply be due to the increased breakdown of glycosphingolipids in lysosomes, as a byproduct of the neurodegenerative process [98]. Similar increases of sphingosine with parallel decreases of myelin markers were observed in the inflammatory demyelination process of multiple sclerosis patients; in this autoimmune process it was shown that the conversion of ceramides to sphingosine can be toxic for oligodendrocytes [99].…”
Section: Figure 2 Targeted Metabolome Analysis Of >12-month-old Atxnmentioning
confidence: 87%